2016
DOI: 10.1130/g37565.1
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for iron mobility during subduction

Abstract: Subduction zones are one of the most important sites of chemical interchange between the Earth's surface and interior. One means of explaining the high Fe 3+ /ƩFe ratios and oxidized nature of primary arc magmas is the transfer of sulfate (SO X), carbonate (CO 3-), and/or iron (Fe 3+) bearing fluids from the slab to the overlying mantle. Iron mobility and Fe stable isotope fractionation in fluids are influenced by Fe redox state and the presence of chlorine and/or sulfur anions. Here we use Fe stable isotopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 32 publications
(49 reference statements)
10
77
1
Order By: Relevance
“…Subsequent devolatilisation reactions progressively release Cl, at the transition from oceanic serpentinites to high-pressure serpentinites, as well as under P-T conditions of antigorite breakdown (Scambelluri et al 2004). In this context, a recent study has revealed an unusual increase in δ 56 Fe in subducted serpentines (from −0.02 ± 0.15 to +0.08 ± 0.11‰; 2σ SD) with the decrease of their Fe 3+ /ΣFe ratio (from 0.7 to 0.5) at the transition from lizardite to high-pressure antigorite (Debret et al 2016). The authors conclude that isotopically light-Fe is carried as Fe(II)-SO X or Fe(II)-Cl 2 species by sulfate-rich and/or hypersaline fluids that are released in the mantle wedge (Debret et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent devolatilisation reactions progressively release Cl, at the transition from oceanic serpentinites to high-pressure serpentinites, as well as under P-T conditions of antigorite breakdown (Scambelluri et al 2004). In this context, a recent study has revealed an unusual increase in δ 56 Fe in subducted serpentines (from −0.02 ± 0.15 to +0.08 ± 0.11‰; 2σ SD) with the decrease of their Fe 3+ /ΣFe ratio (from 0.7 to 0.5) at the transition from lizardite to high-pressure antigorite (Debret et al 2016). The authors conclude that isotopically light-Fe is carried as Fe(II)-SO X or Fe(II)-Cl 2 species by sulfate-rich and/or hypersaline fluids that are released in the mantle wedge (Debret et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a recent study has revealed an unusual increase in δ 56 Fe in subducted serpentines (from −0.02 ± 0.15 to +0.08 ± 0.11‰; 2σ SD) with the decrease of their Fe 3+ /ΣFe ratio (from 0.7 to 0.5) at the transition from lizardite to high-pressure antigorite (Debret et al 2016). The authors conclude that isotopically light-Fe is carried as Fe(II)-SO X or Fe(II)-Cl 2 species by sulfate-rich and/or hypersaline fluids that are released in the mantle wedge (Debret et al 2016). While the Fe isotope database for ultrabasic and basic rocks is growing substantially, further work is required to understand Fe mobility and isotope fractionation in subduction-related basaltic rocks of blueschist and eclogite facies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serpentinization reactions on the seafloor transform olivine to magnetite, releasing H 2 -rich fluids and leaving the oceanic lithosphere with a more oxidized magnetite-bearing assemblage. If high pressure, high temperature deserpentinization reactions transform magnetite back to olivine, the fluids produced from that reaction must contain oxidized components (e.g., SO x species) [Debret et al, 2016]. Similarly, amphibole can contain Fe 31 and the breakdown reactions that produce H 2 O-rich fluids that would equilibrate with that oxidizing assemblage.…”
Section: Geochemical Constraintsmentioning
confidence: 99%